A Collaborative Project Management and Tracking System for UUM Based on Multi Agent Interface - Mzher, Anwar Adnan (2010)
This project aims to build, implements, and evaluate a collaborative project management and tracking system for UUM. A multi agent interface will be used in term of facilitating and improving the data representation of student's projects that assigned for a certain lecturers. Providing a collaborative application for managing and classifying data contents are mostly an important and in particular the UUM Applied Science Division requires managing and tracking student project in more flexible and interactive way. This project will apply a modified Object-Oriented approach for software development to model and implement the propose system. The system will be tested and evaluated in term of usefulness.